Increasing The Activity And Ability Students to Speak English at The Fourth Grade of Hubbulwathan Islamic Boarding School - Babaroza, Muhammad (LPPM STMIK Dharmapala Riau, 2024)
This study aims to find out about student’s activity and ability to speak English in the fourth grade of the Hubbulwathan Islamic Boarding School. The study was descriptive in nature. The purpose of this study is to evaluate the meaning and effectiveness of the language activity that has been implemented at Hubbulwathan Islamic Boarding School in order to increase students’ speaking ability at the fourth grade. The language activity, an English speaking class, will be evaluated by measuring student’s speech production, listening comprehension, reading comprehension and vocabulary. This aims to summarize effective strategies for increasing the activity and ability of fourth-grade students to speak English at Hubbulwathan Islamic Boarding School. Previous studies have investigated the language attitude of Islamic boarding school students towards English, the need for learning English at Islamic boarding schools, investigating the problems of English speaking of the students of Islamic boarding school program, improving students' speaking through communicative language teaching method, and improving students' English speaking proficiency in Saudi public schools. Based on these studies, the following strategies can be implemented: creating a positive language learning environment, motivating students to learn English, using communicative language teaching method, providing suitable and interesting materials, and conducting regular assessments. These strategies can help teachers at Hubbulwathan Islamic Boarding School to improve their fourth-grade students' English-speaking skills and achieve success in learning the language.